A review on advanced nanoparticle-induced polymer flooding for enhanced oil recovery. (23rd November 2022) - Kakati, Abhijit; Bera, Achinta; Al-Yaseri, Ahmed
Graphical abstract: Abstract: In recent times, the application of nanoparticles has been studied by researchers for use in enhanced oil recovery (EOR). This article presents a comprehensive review of recent advancements in nanoparticles-assisted polymer flooding for enhanced oil recovery. The effect of nanoparticles in polymer flooding including viscosity modification, sweep efficiency improvement, wettability alteration, interfacial tension reduction and adsorption control etc. are reviewed with their recent advancements. Experimental studies, including micromodel experiments, are also discussed to understand the efficiency and effectiveness of the nanoparticle-augmented polymer slug in oil recovery. Modelling and simulation work conducted to understand polymer and nanoparticles-assisted polymer flooding processes are highlighted. Challenges and future prospects of nanoparticles-assisted polymer flooding are also elaborated on for understanding the importance of the topic. Finally, the conclusions from the reviewed literature along with future recommendations are presented.